Neuro-ophthalmological abnormalities in cerebrovascular disease - Mykola Klymenko; Viktor Ziuzin; Oksana Borysenko (Ukrainian Society of Ophthalmologists, 2024)
Purpose: To assess the incidence of various neuro-ophthalmological symptoms in patients with chronic cerebrovascular disease (CVD). Material and Methods: This study was conducted at the clinical departments of the Petro Mohyla Black Sea National University (Mykolaiv) in 2018-2022. Two hundred and sixteen patients with CVD were involved in the study. Mean patient age was 62.3 ± 1.2 years and most patients (133 or 60.2%) were males. A neuroophthalmological examination included visual acuity testing, intraocular pressure measurement, perimetry, type of vision and heterophoria assessment, evaluation of ocular motility, convergence, and strabismus in the cardinal positions of gaze, and ophthalmoscopy. In addition, patients had optical coherence tomography with Оptovue Avanti XR apparatus, if indicated. Results: Of 216 patients, 45 (20.8%) had cerebral small-vessel disease, 157 (72.7%), a prior history of transient ischemic attack (TIA), and 118 (46.1%), a prior history of acute cerebrovascular events (ACVE). All patients exhibited signs of hypertensive angiopathy. Of 216 patients, 22 (10.2%) had grade 3, and 6 (2.8%), grade 4 hypertensive angiopathy. There was evidence of posterior ischemic optic neuropathy in the presence of cerebral small-vessel disease in 27 patients (12.5%). Retinal microvascular changes were seen in 133 patients (61.6%). In addition, 10 patients (4.6%) exhibited isolated retinal hemorrhages, 16 (7.4%), hard exudates, and 1 (6.3%) cotton-wool exudates. Moderate retinal and optic disc edema was seen in 23 patients (10.6%). Isolated homonymous visual field defects were found in 13 patients (6.0%); all these patients had a prior history of ACVE. Conclusion: In patients with CVD, we found fundus changes which were mostly ischemic and more severe in the presence of cerebral small-vessel disease. There is a need for an integrated multispecialty/interdisciplinary approach to further research on the neuroophthalmological aspect of CVD.